Therapeutic potential of Thabasir in Sri Lankan Indigenous Medicine: A scientific review: Shifra A.S.F.*, Fahamiya N., Shiffa M.S.M. and Rifna M.R.F. (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Thabasir (Bamboo salt) is a white silica exudation found in the internodes of stems of the female bamboo (Bambusa arundinacea). This concrete like crystalline is an opaque, white, irregular shaped, light, soft and brittle substance. It contains 90 % silica as a hydrate of silicic acid, peroxide of iron, potash, lime, aluminium and vegetable matter. Traditionally it has been used in various ailments such as hyperdipsia, diarrhoea, vomiting, heart diseases, cough, asthma, jaundice, fever, tuberculosis, bronchitis, leprosy, paralytic complaints, anaemia and as a general tonic in convalescents. Further, in recent years scientists have shown more interest in Thabasir due to its medicinal, nutritional and cosmetic values. However, up to now, no research studies have been carried out to prove its therapeutic effects scientifically, as mentioned in Unani medicine. Therefore, the information available in this review would help to do further research in this regard. Hence, this review aims to explore the information available in the literature regarding therapeutic potential of Thabasir in the field of indigenous medicine. All the available information on Thabasir was compiled from search engines of electronic databases such as Google scholar, PubMed, Medline, Scopus and classical texts. The literature search revealed that Thabasir possess pharmacological properties such as cardiac exhilarant, cardiac tonic, astringent, cooling, dessicant, febrifuge, general tonic, sexual tonic, tissue builder, aphrodisiac, spermopiotic, thirst quencher, hemostatic, expectorant, diuretic and general tonic. It can be concluded that Thabasir is a potential therapeutic agent in Sri Lankan indigenous medicine.